An optimal circular antenna array design considering mutual coupling using heuristic approaches. Issue 11 (20th August 2020) - Das, Avishek; Mandal, Durbadal; Kar, Rajib
Abstract: This article shows the design of a non‐uniformly excited single ring circular antenna array (CAA) for the synthesis of optimal far‐field radiation characteristics. A recently proposed meta‐heuristic based optimization algorithm called gray wolf optimization (GWO) and state‐of‐the‐art swarm intelligence based evolutionary optimization technique known as particle swarm optimization with a distribution based update mechanism (PSOd) are individually applied to determine the optimum set of current excitation amplitude weights and the inter‐element spacing among the array elements to reduce the side lobe level and 3‐dB beamwidth considering the mutual coupling. The results obtained by employing PSOd and GWO are compared to those of the uniform radiation pattern and the recently published results of state‐of‐the‐art literature having equal sets of elements to show the superiority of employed approaches. Three different design examples of 8, 10, and 12 elements CAA are reported in this article to study the performances of PSOd and GWO algorithm‐based results over the results of other recently reported literature.